2021
DOI: 10.1002/vms3.570
|View full text |Cite
|
Sign up to set email alerts
|

Physiological, oxidative and metabolic responses of lactating water buffaloes to tropical climate of South China

Abstract: Background Heat stress in tropics is generally associated with significant economic losses resulting from reduced performance, morbidity, and mortality of livestock. To avoid serious consequences of heat stress, it is imperative to better understand the physiological responses and biochemical changes under the state of altered body homeostasis during different seasons of the year. Objectives This study aimed to evaluate the seasonal dynamics of physiological, oxidative and metabolic responses of lactating Nili… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 47 publications
0
2
0
Order By: Relevance
“…RT is a sensitive indicator of the physiological response to heat stress, as it is nearly constant under normal conditions [ 37 ]. However, some authors have reported no significant differences in the RT at different THI levels or seasons on non-lactating buffaloes [ 38 , 39 ]. This is not surprising, since calves and heifers generate less metabolic heat than lactating cows [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…RT is a sensitive indicator of the physiological response to heat stress, as it is nearly constant under normal conditions [ 37 ]. However, some authors have reported no significant differences in the RT at different THI levels or seasons on non-lactating buffaloes [ 38 , 39 ]. This is not surprising, since calves and heifers generate less metabolic heat than lactating cows [ 40 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have mostly focused on the effects of diseases like mastitis or acidosis in cattle [ 20 , 26 , 42 , 43 ], but few studies have been reported in buffalo [ 30 , 38 , 39 ]. There are a number of biomarkers that can be used to monitor oxidative stress; however, differences in the endpoints and methodologies used to investigate the oxidant and antioxidant markers make the comparison between studies meaningless, even for studies quite similar [ 38 ]. For instance, Megahed G.A., et al [ 34 ].…”
Section: Discussionmentioning
confidence: 99%